Microdebrider: a painless and effective technique for adenoidectomy; comparative study with curette assisted adenoidectomy - Ken, Akanksha; Tripathy, Smruti Milan (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2021)
Background: Adenoid is a nasopharyngeal tissue which forms Waldeyer’s ring as said by Meyer, 1968. Adenoids become demonstrable with signs of CSOM with adenoid hyperplasia, recurrent rhino-sinusitis, characteristic ‘adenoid facies’, nasal obstruction, mouth breathing, snoring, drooling of saliva and speech abnormalities and dental malocclusion. Adenoidectomyis the common surgery done using various techniques like curette, microdebrider and many more. In this study we evaluate and compare the efficacy of adenoidectomy by microdebrider verses curette assisted adenoidectomy. Aim of the study was to evaluate and compare the efficacy and benefits of adenoidectomy by microdebrider with curette assisted adenoidectomy. Methods: This is a prospective randomized single-blind study done for 1 year. Total 150 patients were included which were diagnosed as adenoid hypertrophy based on clinical and radiological examination and were equally divided in 2 group for both the procedures (curette and microdebrider). Results: Patients show good response to the treatment with microdebrider assisted adenoidectomy with less complication and early recovery. Conclusions: We observe that proper examination and early surgical intervention using modern technique i.e., microdebrider reduces the time, residual tissue with less complication and promote early recovery.